Effect of Root Canal Filling Materials and Pretreatment with Solvents on the Shear Bond Strength of Composite Resin with Primary Tooth Dentin. (2nd April 2021) - Ghouchani, Taraneh Zeynalzade; Farhadpour, Hajar; Mohammadi, Najmeh
Abstract : Aim . Root canal filling materials have the tendency to inhibit adhesion of resin-based composites. This study was aimed at evaluating the effect of root canal filling materials and their solvents on the shear bond strength (SBS) of resin composite with the primary tooth dentin. Methods and Materials . Seventy-two intact anterior primary teeth were selected. Smooth dentinal surfaces were prepared to a minimum diameter of 3 mm and thickness of 1.5–2.0 mm. The samples were equally divided into six groups (n = 12 ). In group 1: control group, no root filling material; in group 2: Metapex, no solvent; in group 3: Metapex+ethanol solvent; in group 4: ZOE, no solvent; in group 5: ZOE+ethanol solvent; and in group 6: ZOE+orange oil solvent were applied. Then, dentin surfaces were etched, and composite restorations were placed and cured. The specimens were stored in distilled water at 37°C for 24 hours. SBS values were determined using a universal testing machine. Results . The SBS values of composite to dentin in groups 2 and 4 were significantly lower than those in the control group (P < 0.001 ). Cleansing of the specimens with 96% ethanol after removal of Metapex significantly increased the composite-dentin bond (P < 0.001 ). Applying ZOE, only orange oil solvent significantly increased the SBS of the composite to the primary tooth dentin (P = 0.01 ). Conclusion . To reduce the negative effects of endodontic root filling materials on the SBS of composite and primary tooth dentin, ethanol is a suitable solvent when Metapex is used, while orange oil might be a better choice than ethanol when applying ZOE.